Locating the locale of local food: The importance of context, space and social relations. Issue 6 (27th October 2014) - Carroll, Brídín E.; Fahy, Frances
Abstract: Localization is one process/outcome that is proffered as key to the 'grand challenges' that currently face the food system. Consumers are attributed much agency in this potential transformation, being encouraged from all levels of society to exert their consumer muscle by buying local food. However, due to the social construction of scale it cannot be said that 'local food' is a definite entity and consumers understand the term 'local food' differently depending on their geographic and social context. As such, the research upon which this paper is based aimed to provide a nuanced understanding of how consumers in the particular spatial and social contexts of urban and rural Ireland understood the concept of 'local food'. A specific objective was to test the theory that these consumers may have fallen into the 'local trap' by unquestioningly associating food from a spatially proximate place with positive characteristics. A three-phase mixed methodology was undertaken with a sample of consumers dwelling in urban and rural areas in both Dublin and Galway, Ireland: 1000 householders were surveyed; 6 focus group discussions took place; and 28 semi-structured interviews were carried out. The results presented in this paper indicate that for most participants in this study, spatial proximity is the main parameter against which the 'localness' of food is measured. Also, it was found that participants held multiple meanings of local food and there was a degree of fluidity in their understandings of the term. The results from the case study regions highlight how participants' understandings of local food changed depending on the food in question and its availability. However, the paper also indicates that as consumers move from one place to another, the meaning of local food becomes highly elastic. The meaning is stretched or contracted according to the perceived availability of food, greater or lesser connections to the local producer community and the relative geographic size of participants' locations. Our analysis of findings from all three phases of this research revealed a difference in understandings of local food among participants resident in urban and rural areas: participants dwelling in rural areas were more likely than those in urban areas to define local food according to narrower spatial limits. The paper concludes with an overview of the practical and theoretical significance of these results in addressing the current dearth of research exploring the meaning of local food for consumers and suggests avenues for future research.